Kreativitas Guru dalam Mengembangkan Media Pembelajaran Digital pada Pembelajaran Sejarah Daring (Studi Deskriptif Terhadap Guru Sejarah SMA Di Kota Bandung) - Endah Febriyanti; Yani Kusmarni; Tarunasena Ma'mur (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This research is motivated by the findings of researcher at the research location which show that in the online history learning process, teacher creativity is needed, one of which is in terms of developing digital learning media. So the study in this research is the creativity of teachers in developing digital learning media in online history learning, with the main problem formulation "how is the creativity of teachers in developing online history learning media?" This study uses a descriptive study that aims at obtaining a description of the creativity of high school history teachers in Bandung City in developing digital learning media based on indicators of flexibility, fluency, originality, and presentation. This includes studying the constraints and efforts as well as student’s responses to the developed media. The results of this study indicate that teachers have developed digital learning media which are realized in several forms, such as slides, videos, and podcasts. However, from the media products that have been developed, podcasts are the media with the most prominent elements of originality compared to others. This shows that there are still several aspects that have not been met based on the findings of each indicator. One of them is caused by the obstacles felt by the teacher both from internal and external factors. However, students still feel helped by the media developed by the teacher to understand the material presented, but it does not mean that all students feel that the media is interesting. This is largely determined by what media the teacher uses during the online learning process.